ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR SISWA SMP BERDASARKAN GENDER - Rismayanti Rismayanti; Mira Octafianti; Sartika Sartika (Departement of Mathematics Education, 2019)
The purpose of this research is to know the mathematical communication ability and interest in learning of students based on gender by using predetermined indicators. The population in this research is the Junior High School students in West Bandung Regency and the samples examined is one of a class of 32 students in class VIII Junior High School in West Bandung Regency. The methods used in this research is qualitative descriptive method using the likert scale with the awarding of the instrument in the form of reserved test description to analyze mathematical communication ability and the granting of the now to analyze interest in learning students. Analysis of the results obtained in this study suggest that mathematical communication skills male students and the female is still classified as low. But students male or female students already have an interest in learning mathematics.